Comic Strip: a Media to Teach English - Rizky Vita Losi; Wahyuni, Sri; Rosida, Sisi; Zahra, Putri (JOLADU: Journal of Language Education, 2023)
When students are asked to write or read any English stories, then they need to learn about vocabulary as well. Writing skill challenges foreign students to be creative to create stories, while reading skill invites students to be good at comprehending the text. Recent studies have claimed in preference for the use of comic strips in language learning. The current study will go into detail about the use of comic strips as a learning medium, its advantages, and the effect to English learning at class. This literature review used George's (2008) model as a research method. The information was gathered from research articles about the use of comic strips in learning languages that were published in trustworthy international journals and recognized national journals. According to the review, prior research has shown that using comic strips in language learning can benefit students with their vocabulary, writing, and reading skills.